Time Course of the Development of Nonalcoholic Fatty Liver Disease in the Otsuka Long-Evans Tokushima Fatty Rat - Yi-Sun Song; Cheng-Hu Fang; Byung-Im So; Jun-Young Park; Yonggu Lee; Jeong Hun Shin; Dae Won Jun; Hyuck Kim; Kyung-Soo Kim (Gastroenterology Research and Practice)
Nonalcoholic fatty liver disease (NAFLD) is considered a hepatic manifestation of metabolic syndrome. In this study, we investigated histological and biochemical changes in NAFLD and the gene expression involving de novo lipogenesis in Otsuka Long-Evans Tokushima fatty (OLETF) rats. We used OLETF rats and Long-Evans Tokushima Otsuka (LETO) rats as animal models of NAFLD and as controls, respectively. Consistent observations were made at 4-week intervals up to 50 weeks of age, and all rats were fed ad libitum with standard food. Biochemical and histological changes were observed, and gene expression involved in de novo lipogenesis was measured using real-time polymerase chain reactions. As a results hepatic micro- and macrovesicular steatosis and hepatocyte ballooning were evident in the OLETF rats at 22–38 weeks of age but disappeared after 42 weeks; no fibrosis or collagen deposition was observed. Gene expression involved in de novo lipogenesis followed a pattern similar to that of the histological changes. In conclusion, in the absence of dietary manipulation, hepatic steatosis in OLETF rats is evident at 22–38 weeks and declines after 42 weeks. Therefore, OLETF rats at 22–38 weeks are recommended as animal models of hepatic steatosis.